2007
DOI: 10.1175/jas3830.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Atmosphere–Ocean Coupling on the Predictability of Monsoon Intraseasonal Oscillations*

Abstract: The impact of air-sea coupling on the predictability of monsoon intraseasonal oscillations (MISO) has been investigated with an atmosphere-ocean coupled model and its atmospheric component. From a 15-yr coupled control run, 20 MISO events are selected. A series of twin perturbation experiments have been conducted for all the selected events using both the coupled model and the atmosphere-only model. Two complementary measures are used to quantify the MISO predictability: (i) the ratio of signal-to-forecast err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 140 publications
(90 citation statements)
references
References 57 publications
(89 reference statements)
5
82
1
Order By: Relevance
“…The present result suggests that air-sea coupling extends MJO forecasting skill by about 1 week. This finding is basically consistent with the result from our previous predictability study of Fu et al (2007), which showed that air-sea coupling extends monsoon intraseasonal predictability by 1 week.…”
Section: Mjo Forecasting Skills In Three Modelssupporting
confidence: 93%
See 1 more Smart Citation
“…The present result suggests that air-sea coupling extends MJO forecasting skill by about 1 week. This finding is basically consistent with the result from our previous predictability study of Fu et al (2007), which showed that air-sea coupling extends monsoon intraseasonal predictability by 1 week.…”
Section: Mjo Forecasting Skills In Three Modelssupporting
confidence: 93%
“…Many previous studies with a hierarchy of models have shown that air-sea coupling improves the simulation and predictability of the MJO (Krishnamurti et al 1988;Flatau et al 1997;Wang and Xie 1998;Waliser et al 1999;Woolnough et al 2000;Fu and Wang 2004;Fu et al 2007Fu et al , 2008Pegion and Kirtman 2008). Using model intraseasonal events as target, Fu et al (2008) showed that the potential predictability of the atmosphere-only runs driven by forecasted daily SST reach very similar level as that of the coupled runs.…”
Section: Important Role Of Air-sea Couplingmentioning
confidence: 98%
“…As such, knowledge of the initial state of the atmosphere is required, as is air-sea interaction for forecasting ISOs . Figure 2 indicates the potential for 20-30 days of rainfall predictability based on numerical experiments initialized with small perturbations to the initial atmospheric state during different phases of the models ISO (Fu et al 2007). …”
Section: Active/break Cyclesmentioning
confidence: 99%
“…Since the MJO is a slow oscillator, it is reasonable to think that the long-range predictability would be from four weeks to two months (e.g., Van den Dool and Saha 1990). The actual skillful prediction of the MJO from numerical and statistical models is currently closer to 15-20 days (e.g., Goswami and Xavier 2003;Fu et al 2007;Jiang et al 2008;Seo et al 2009) with a theoretical upper limit of ;30 days that was put forth by Waliser et al (2003). So, we can likely obtain skillful forecasts of the future state of the MJOI with a lead time of at least two weeks making the MJOI a viable long-term forecast tool.…”
mentioning
confidence: 99%